Qualitative organizational research : core methods and current challenges - Symon, Gillian; Cassell, Catherine (Los Angeles, CA. : SAGE, 2012)
This comprehensive text brings together in one volume the range of methods available for undertaking qualitative data collection and analysis. Qualitative Organizational Research contains 27 chapters, each focusing on a specific technique. The first part of the volume looks at contemporary uses of qualitative methods in organizational research, outlining each method and illustrating practical application through case studies. The second part of the volume goes on to consider the broader issues in qualitative methods, examining key contemporary debates in each area as well as providing practical advice for those undertaking organizational research. Written by Gillian Symon and Catherine Casse internationally renowned experts in qualitative research methods, this text is an accessible and essential resource for students and researchers in the areas of organization studies, management research and organizational psychology.
Includes bibliographical references and index.
Keywords: Organizational sociology -- Research -- Methodology; Organizational behavior -- Research -- Methodology; Qualitative research